Fostering EFL Students’ Speaking Skills through The Pen Pals Project in The Cross-Cultural Understanding Course - Intan Nurul Afiqoh; Titis - Sulistyowati; Agung Dwi Nurcahyo (Universitas Muhammadiyah Semarang, 2026)
The Pen Pals Project was exciting and challenging in improving my speaking skills. The pen pals project, which is based on cross-cultural knowledge between countries, is one of the efforts that can be used to enhance students’ speaking skills. However, previous studies have primarily focused on students’ writing skills at the junior and senior high school education levels. This motivates the researcher to further uncover the benefits of the pen pals project in a cross-cultural understanding course that aims to improve speaking skills. This study aims to determine how much the pen pals project can improve students’ speaking ability. It focuses on how much the pen pals project can improve students’ speaking skills. The data were gained from students’ perspectives and experiences during the project. This research uses a qualitative descriptive method. Researchers used a questionnaire concerning scale-based students' perspectives. This study also used semi-structured interviews as a research instrument. The result of this study indicates that a favorable percentage of the pen pals project contributed to improving students’ speaking skills. Student perspectives showed that students could carry out the project with enthusiasm, curiosity, and happiness. This improvement is marked by positive emotional, behavioral, and cognitive engagement. Then, practically, students also experienced improvements in pronunciation, vocabulary, fluency, grammar, and comprehension.Keywords: cross-cultural understanding; engagement; pen pals project; speaking skills